6-[18F]Fluoro-L-DOPA: A Well-Established Neurotracer with Expanding Application Spectrum and Strongly Improved Radiosyntheses. (28th May 2014) - Pretze, M.; Wängler, C.; Wängler, B.
Abstract : For many years, the main application of [ 18 F]F-DOPA has been the PET imaging of neuropsychiatric diseases, movement disorders, and brain malignancies. Recent findings however point to very favorable results of this tracer for the imaging of other malignant diseases such as neuroendocrine tumors, pheochromocytoma, and pancreatic adenocarcinoma expanding its application spectrum. With the application of this tracer in neuroendocrine tumor imaging, improved radiosyntheses have been developed. Among these, the no-carrier-added nucleophilic introduction of fluorine-18, especially, has gained increasing attention as it gives [ 18 F]F-DOPA in higher specific activities and shorter reaction times by less intricate synthesis protocols. The nucleophilic syntheses which were developed recently are able to provide [ 18 F]F-DOPA by automated syntheses in very high specific activities, radiochemical yields, and enantiomeric purities. This review summarizes the developments in the field of [ 18 F]F-DOPA syntheses using electrophilic synthesis pathways as well as recent developments of nucleophilic syntheses of [ 18 F]F-DOPA and compares the different synthesis strategies regarding the accessibility and applicability of the products for human in vivo PET tumor imaging.